Enhanced mechanical properties of poly (ε-caprolactone) nanofibers produced by the addition of non-stoichiometric inclusion complexes of poly (ε-caprolactone) and α-cyclodextrin. (12th October 2015) - Narayanan, Ganesh; Gupta, Bhupender S.; Tonelli, Alan E.
Abstract: A unique nanofibrous structure consisting of poly (ε-caprolactone) (PCL) and non-stoichiometric α-cyclodextrin-poly (ε-caprolactone) inclusion complexes [(n-s)-PCL-α-CD-ICs] was produced by electrospinning. For electrospinning experiments, stoichiometric ratios of the (n-s)-PCL-α-CD-ICs, their percentage loading, and the concentration of the PCL solutions were varied. With their partially un-included guest PCL chain portions, the effects of the (n-s)-PCL-α-CD-ICs on the thermal behavior and mechanical properties of the PCL nanofibers have been investigated. SEM indicated that at lower PCL concentrations (12%), loading of up to 15% (n-s)-PCL-α-CD-ICs resulted in bead-free fibers. However, at 14% PCL concentration, bead-free fibers were obtained only until 10% loading; beyond this loading, some beads were observed. DSC analyses indicated, compared to neat PCL nanowebs, there were significant increases in the melting and the crystallization temperatures of the PCL/(n-s)-PCL-α-CD-IC nanowebs. Absence of water loss and enhanced thermal stability of α-CDs was observed by TGA analyses, which indicated the presence of α-CDs threaded by PCL chains. Mechanical properties of the composite webs indicated, with the addition of the ICs, the tensile modulus and ultimate tensile strength of the composite fibers increased significantly (200–400% for the modulus) over those of neat PCL or uncomplexed PCL/α-CD nanofibers. At the same time, their extensions at break were reduced by factors of ∼ (2–3). With better mechanical and stiffness properties, these novel nanocomposite fibers, which are non-toxic, but biodegradable and biocompatible, would be potential candidates as scaffolds for various applications. Graphical abstract: Schematic illustration of the suggested morphologies of PCL nanowebs containing (n-s)-PCL-α-CD-ICs. The un-included PCL chain portions of the (n-s)-PCL-α-CD-ICs serve to nucleate and increase the crystallization of the unthreaded matrix PCL chains. In addition, intimate crystallization of unthreaded matrix PCL chains and un-included PCL chain portions of (n-s)-PCL-α-CD-ICs serve to tie them together. Both of these factors lead to significant increases in nanoweb strength and concomitant decreases in their elongation. Highlights: We prepared two non-stoichiometric inclusion complexes (ICs) of PCL and α-cyclodextrins. Nanocomposites containing these two ICs as nucleating agents for bulk PCL were prepared. Nanocomposites were evaluated for thermal and mechanical properties. Testing indicated a tremendous increase in mechanical properties, compared to Neat PCL.